Feeding the World: How Tariff and Quota Policies Influence Global Food Sales Volumes-An Indonesian Perspective - Nurhayati (Yayasan Ilomata, 2024)
This research seeks to assess the impact of Indonesia's tariff and quota policies on global food trade. It uses the Systematic Literature Review technique to thoroughly analyse the impact of various trade policies on market dynamics, with a particular focus on economic, social and environmental dimensions. The results emphasise Indonesia's important position in the world food market, providing valuable insights into the complex relationship between national priorities and international trade responsibilities. It highlights the importance of these rules in influencing global trade tactics, providing crucial insights for policymakers, economists, and business executives. This extensive analysis examines Indonesia's strategic impact and the wider consequences of its policies on global food security and market stability. The research implications are an important reference for understanding the complex dynamics of global market forces, focusing on the delicate balance between national policymaking and international trade commitments.